Tumor necrosis factor alpha-308 gene polymorphism in patients with anorexia nervosa - Kanbur, Nuray; Mesci, Lütfiye; Derman, Orhan; Turul, Tuğba; Çuhadaroğlu, Füsun; Kutluk, Tezer; Tezcan, İlhan (The Turkish Journal of Pediatrics, 2008)
Tumor necrosis factor alpha (TNF-alpha) is a principal cytokine that may induce weight loss. TNF-alpha -308 G to A polymorphism increases transcription of TNF-alpha in vitro. The aim of this study was to investigate whether TNF-alpha gene promoter polymorphism at position -308 (G to A substitution) is one of the factors playing a role in the development of anorexia nervosa (AN). Sixteen patients with AN, aged 11-20 years, were included in this study, and 5/16 (31%) patients had TNF-alpha -308 G/A genotype. In the control group, 12/174 (7%) had -308 G/A genotype. There was a significant statistical difference between the patient and control groups (p=0.007). The minimum body mass index (BMI) values ever recorded for each patient during the course of the disease were significantly higher in the five patients with TNF-alpha -308 G to A polymorphism (p= 0.003). TNF-alpha gene promoter polymorphism at position -308 might be associated with a predisposition to AN and initiate the disease. The protective mechanisms that affect clinical manifestation of the disease may be related with other anti-inflammatory cytokines or immunologic mechanisms.